Teses & Dissertações - da Silva, Dafne Reis Pedroso; Dalpiaz, Jamile Gamba; Santi, Vilso Junior Chierentin; Rocha, Mário Eugênio Villas-Boas; Barros, Roberta Coelho; Luersen, Eduardo Harry; Nunes, Ana Cecília Bisso; Osório, Moreno Cruz; Reis, Breno Maciel Souza; Macedo, Robson Arthur Sarmento; et al. (Revista FAMECOS, 2013)
Doutorado